Non-Evental Novelty: Towards Experimentation as Praxis - Human, Oliver (Cosmos and History: The Journal of Natural and Social Philosophy, 2013)
<!--[if gte mso 9]> <![endif]--> In this article I explore the possibilities of experimentation as a non-foundational praxis for introducing novel ways of being into existence. Beginning with a discussion, following Bataille, of the excess of any thought, I argue that any action in the world is necessarily uncertain. Using the insights of Derridean deconstruction combined with Badiousian truth procedure I argue that experimentation offers a means for acting from this uncertain position. Experimentation takes advantage of the play and uncertainty of our understanding of the world as a means of moving towards more progressive political positions. <!--[if gte mso 9]> Normal 0 false false false EN-IE X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->